Multiplication végétative de ximenia americana l. par drageonnage - Guidawa Fawa; Pierre Marie Mapongmetsem; Jean Baptiste Noubissie-Tchiagam; Ronald Bellefontaine (VertigO)
In the Guinean savannah Highlands of Cameroon, X.americana L. is an important socio-economic species facing high zoo-anthropic pressure. The objective of the study is to characterize the natural and artificial suckering of the species. An inventory has been realized in March 2011 in 20 square plots of 1ha in the savannah of Dang to evaluate relative frequency of adult trees which sucker. A total of 633 trees of X.americana have been inventoried, among which 22 kept suckers. Artificial suckering induction trials by simple wound and by complete sectioning have been undertaking on superficial roots during March 2011 on 137 adult trees of different ages that 70 % were multicaules. Ten months after the initiation, it appears that the artificial complete sectioning is more efficient (86.67 %) than the simple wound (60 %). Among the two types of induction, the roots exposed to the open air have presented a successful percentage than that covered by soils. Induced suckers appear in majority in distal pole of the mother root. This Olacaceae presents a good aptitude to artificial suckering. Nevertheless during ten months of observation, none sucker has initiated its own rooting system. This low cost technique could constitute an important step in the domestication process of this plant, if complementary studies during a long observation periods which can permit to precise vigorous root neoformation which can permit a disconnection with the mother tree and an important growth.